Analisis Kemampuan Berpikir Kreatif Matematis Ditinjau dari Kecemasan Matematika Peserta Didik - Andi Nabilah Ridwan; Sriyanti, A.; Rahman, Ulfiani; Munirah (Alauddin Journal of Mathematics Education, 2025)
Creative thinking skills are essential in mathematics learning. Although very important, in reality, students' creative thinking skills are still low. On the other hand, there are also factors that need to be considered in mathematics learning, namely mathematics anxiety. Students are sometimes unable to solve problems well, feel afraid, and lack confidence when faced with mathematics lessons. This study aims to determine the ability of mathematical creative thinking in terms of mathematics anxiety of grade X students of SMA Negeri 8 Bulukumba. This type of research is descriptive research with a qualitative approach. This research was conducted at SMA Negeri 8 Bulukumba with research subjects of grade X.2 students totaling 32 people in the 2023/2024 academic year. Data collection techniques in this qualitative study were mathematics anxiety questionnaires, mathematical creative thinking ability tests, interviews, and to validate the data using data triangulation techniques. The results of the study showed that students with low category of mathematics anxiety were able to fulfill all indicators of mathematical creative thinking ability optimally. This occurs because students with low levels of anxiety tend to be more confident in understanding problems, exploring various alternative solutions, and explaining their thinking in detail so that the indicators of fluency, flexibility, originality, and elaboration can be achieved. Students with moderate anxiety are only able to meet the indicators of fluency, flexibility, and originality, because although they are able to produce various solutions and strategies, the anxiety they still feel makes them less in-depth or detailed in the solutions provided. Meanwhile, students with high anxiety are only able to meet the indicators of fluency and elaboration, due to the fear of making mistakes and mental pressure that prevents them from thinking flexibly and original in finding solution strategies. This study contributes by providing empirical evidence that managing mathematics anxiety is necessary for students' mathematical creative thinking abilities to develop optimally.